CHOOSING THE BEST ARCHITECTURE FOR MOBILE APPLICATIONS - Farooq Abdulla Mulla, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This comprehensive article explores the critical aspects of mobile application architecture, examining how architectural decisions impact both immediate functionality and long-term maintainability. The article covers key areas including architectural foundations, modularization strategies, performance optimization, security implementation, testing methodologies, and future considerations. Through extensive analysis of industry practices and research findings, the article demonstrates how well-structured architectures contribute to improved development efficiency, enhanced user experience, and better application performance. The article provides insights into various architectural patterns, their specific use cases, and their impact on different aspects of mobile application development, while also addressing crucial considerations for security, testing, and maintenance practices.